1987
DOI: 10.1055/s-2006-962744
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Essential Oil Yield and Composition ofThymus hyemalis

Abstract: The aerial parts of THYMUS HYEMALIS Lange were collected throughout its complete vegetative cycle (April 1981 to March 1982) from the same locality. The yield and composition of essential oil have been determined in eleven samples with special reference to the content of 1,8-cineole, camphor, thymol, and carvacrol. It was found that the yield and composition of the oil changed from month to month. On the basis of the results obtained, July might be proposed as the most suitable month for harvesting T. HYEMALIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 1 publication
1
19
0
2
Order By: Relevance
“…Golmakani and Rezaei extracted essential oils from thyme with HD and reported the yield of 2.39% (wt.%). Cabo et al (1987) collected the aerial parts of Thymus hyemalis Lange throughout its complete vegetative cycle and reported that the essential oil content varying from 0.15% on December 23 to 0.58% on July 4 of the next year. Similar results were reported for T. vulgaris L. (2-and 5-year old plants) (Hudaib, Speroni, Di Pietra, & Cavrini, 2002).…”
Section: Comparison Of Extraction Kinetics and Extraction Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Golmakani and Rezaei extracted essential oils from thyme with HD and reported the yield of 2.39% (wt.%). Cabo et al (1987) collected the aerial parts of Thymus hyemalis Lange throughout its complete vegetative cycle and reported that the essential oil content varying from 0.15% on December 23 to 0.58% on July 4 of the next year. Similar results were reported for T. vulgaris L. (2-and 5-year old plants) (Hudaib, Speroni, Di Pietra, & Cavrini, 2002).…”
Section: Comparison Of Extraction Kinetics and Extraction Yieldmentioning
confidence: 99%
“…23). The essential oil composition of T. vulgaris can be influenced by harvest time, ecological and climatic conditions (Cabo et al, 1987;Putievsky & Basker, 1977). Many authors have reported that T. vulgaris oil components change by different ecological regions, growing conditions, harvest time and years (Baranauskiene et al, 2003;Kastner, 1969;Özgüven & Stahl-Biskup, 1989;Özgüven & Tansi, 1998;Piccaglia & Marotti, 1991).…”
Section: Gc-msmentioning
confidence: 99%
“…Essential oil constituents and secondary metabolites in medicinal and aromatic plants are strongly influenced by their origin, environmental conditions, ontogenetic variation [11,12], management practices (e.g., harvest time), and ecological and climatic conditions [13]. Therefore, antimicrobial, antioxidant, and other biological activities may vary, based on the variations in chemical compositions of essential oils and the extracts of medicinal plants [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…b Minimum inhibitory concentration, values as mg/mL. c Oxa: oxacillin (1 μg/disk), Tet: tetracycline (30 μg/disk); Amox: amoxicillin (10 μg/disk); Keto: ketoconazol (20 μg/disk); Gen: gentamicine (30 μg/disk);(7)(8)(9)(10)(11)(12)(13)(14), moderately active; ( > 14), highly active; NA, not active. to you by | Dalhousie University Authenticated Download Date | 6/22/15 10:13 PM…”
mentioning
confidence: 99%
“…These compounds can delay or inhibit the oxidative damage caused by free radicals and can protect us against major diseases such as coronary heart disease and cancer in human 9,[13][14][15][16] . The yield of plant material, essential oil composition and secondary metabolites in medicinal and aromatic plants are strongly influenced by harvest time, ontogenetical variation and environmental factors such as soil type and nutriton 9,[17][18][19] . Knowledge of the factors that influence on yield and essential oil composition in medicinal plants is insufficient, and these factors seems to play a important role in drug yield and essential oil composition in medicinal and aromatic plants.…”
Section: Introductionmentioning
confidence: 99%